A Study On Uropathogens In Diabetic Patients from a tertiary care Hospital in Kanchipuram - S, Sivasankari; S, Senthamarai; C, Anitha; SK, Amsavathani; V, Venugopal (Journal of Research in Biology, 2012)
Diabetes has long been one of the predisposing factors of UTI. There were several studies about the role of DM in etiology and resistance pattern of uropathogens with UTI. Hence this study was aimed to know the prevalence of Asymptomatic Bacteriuria (ASB) among diabetic patients Materials and Methods: This Study was conducted from May 2008 - Oct 2009. A total of 220 urine samples were collected from patients above 40yrs who attended the OPD with the history of diabetes and 100 urine samples were collected from non diabetics patients screened for and asymptomatic bacteriuria (>105 CFU /ml Urine). All urine samples were processed according to the standard protocol. Antibiotic sensitivity was done by kirby Bauer disc diffusion method. Results: Out of 220 diabetic patients, 52 had significant bacterial growth, and out of 100 non diabetic patients 22 had significant growth. UTI was more common in female patients in diabetes but more common in males in non diabetes. E.coli was the commonest isolate in both diabetic and non diabetic patients. The antibiotic resistance pattern in diabetics and non diabetics were found to be similar. Conclusion: Our study with asymptomatic UTI in diabetes mellitus, shows the antimicrobial resistance patternfor formulating antibiotic policies.